The effect of cold plasma treatment on seeds towards the growth rate of vegetable plants - Emyliea Zolkafle, 1993- , author; Zolkafle Buntat; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2017